Islamic Ethics & Medical Jurisprudence Ethical Consideration for Medical Volunteers in War & Disaster Zone - Yahaya, Ahmad Yusuf; Mohamed Hatta, Muhammad Munawar bin; Ifwat Ishak, Muhammad Shahrul (International Journal of Human and Health Sciences (IJHHS), 2025)
Ethics can be defined as behavior based on ideas about what is morally good and bad. In Islam ethics is defined as akhlaq which means character, nature, and disposition, assumes a good relationship between the Creator and its creation, and vice versa. Good behavior principles are developed in the humanitarian world to govern a person’s or group’s behavior during relief activity. The International Red Cross and Red Crescent (ICRC) Movement developed the seven Fundamental Principles to ensure that the actions of volunteers and health workers are in the best interests of the people it seeks to serve. Later these principles were further described in the Code of Conduct in Disaster Relief. It reaffirms the basic humanitarian principles of humanity, impartiality, and independence and includes more recent development concepts such as respect for culture, participation, sustainability, accountability, and dignity. The Sphere project, launched by a group of humanitarian agencies is an initiative to improve the conduct of disaster relief operations. One of the main pillars of the Sphere project is the Humanitarian Charter and Minimum Standards in Disaster Response. All these guidelines are best practices in relief and mostly conform to Islam. Islamic ethics calls for mankind to undertake a continuous process of selfpurification, in thought, feelings, and emotions; in social interactions through intentions and deeds that benefit other human beings as well as other creations of Allah; in using the resources that Allah has wisely given him; and in bringing him closer to the ideal as described by the Prophet: “the best amongst you are those who are the owners of the best morality. International Journal of Human and Health Sciences Supplementary Issue 01: 2025 Page: S23